The Relationship Between VARK Learning Styles and Students’ Perceptions of the Classroom Learning Environment - Alifia Dewi Hariyani; Susy Budi Astuti; Prasetyo Wahyudie; Anggri Indraprasti (JETL (Journal of Education, Teaching and Learning), 2025)
This study examined elementary school students’ learning style preferences based on the VARK (Visual, Aural, Reading/Writing, and Kinesthetic) model and aimed to explore how these preferences relate to students' perceptions of the classroom learning environment. A quantitative approach was used, involving 120 sixth-grade students at an elementary school in Pontianak. Data were collected through the VARK questionnaire and the classroom environment perception questionnaire. Data were analyzed using descriptive statistics and One-Way ANOVA to identify the distribution of learning styles and examine differences in students' perceptions of the classroom environment. The findings indicated that unimodal learning styles were more dominant, with kinesthetic as the most common preference among students. The analysis revealed no significant differences in students’ perceptions of the classroom environment across the various learning style groups. These findings suggest that although students have different learning preferences, they tend to perceive the classroom environment in similar ways. Therefore, understanding students’ learning styles can support the development of more responsive and inclusive learning environments in elementary schools.